A progress on the development of mathematical model on two-phase flow over a vertical stretching sheet - Aljabali, Ahlam; Abdul Rahman, Mohd Kasim; Ayman, Mohd Hussein (IOP Publishing, 2019)
The investigation on flow and heat transfer are important in the engineering applications, for example, extrusion of metal and polymer, cooling of electronic devices, heat exchanger and chemical processing equipment. Since the investigations on the real applications are costly and sometime hazardous, the study on mathematical model representing the fluid flow and heat transfer’s problem is considered to overcome this limitation. This paper will present the progress on the development of mathematical model on non-Newtonian two-phase model where the fluid flow is studied together with the dust particles. The review will include the discussions on existing problems, its methodology as well as the significance outcomes. The main contributions on this paper is to present the research gap and the possible development for future investigations on the problem under the mathematical model of fluid flow and heat transfer.